Thermal behavior of nitrocellulose-based superthermites: effects of nano-Fe2O3 with three morphologies. Issue 38 (28th April 2017) - Zhang, Ting; Zhao, Ningning; Li, Jiachen; Gong, Hujun; An, Ting; Zhao, Fengqi; Ma, Haixia
Abstract : Superthermites with three Fe2 O3 morphologies (rod-like, polyhedral, and olivary) were synthesized. The morphological effects of Al/Fe2 O3 on the thermal decomposition property of nitrocellulose (NC) were investigated. Abstract : Superthermites or metastable intermolecular composites (MIC) are well-known for their excellent combustion characteristics in propellants. Herein, superthermites with three Fe2 O3 morphologies (rod-like, polyhedral, and olivary) were synthesized. The effects of Al/Fe2 O3 on the thermal decomposition property of nitrocellulose (NC) were investigated in detail via differential scanning calorimetry (DSC). The results indicate that the catalytic performances of the superthermites are highly relevant to the specific surface area of their corresponding Fe2 O3 . Al/Fe2 O3 containing rod-like Fe2 O3 (Fe2 O3 (r)) shows a much improved performance compared with other morphological samples. The values of apparent activation energy ( E a ) and thermal ignition temperature ( T beo ) of NC-Al/Fe2 O3 (r) were the lowest. This study could provide some directive reference data for the thermal behavior of nitrocellulose-based superthermites.